2008
DOI: 10.1159/000124276
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Diagnostic Value of Electrical Ear Canal Stimulation in Cochlear Implant Candidates by Functional Magnetic Resonance Imaging

Abstract: Prior to cochlear implant (CI) surgery in children, the integrity of the auditory pathway is sometimes assessed by electrical ear canal stimulation (ECS). However, the evaluation of reactions as auditory is subjective. To test the prognostic value of ECS, functional magnetic resonance imaging (fMRI) was performed during ECS vicariously in 18 adult CI candidates. Activation of the primary auditory cortex was detected in 9 of 16 cases when auditory sensations during ECS occurred, and tended to be more bilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…This is in line with earlier results. 5 , 7 A possible limitation in the current study is the use of open-set bisyllabic word recognition test in quiet as a marker for speech perception and CI outcome in general. Other audiological tests, such as nonsense syllable, word, phrase or sentence tests, might de more appropriate in judging speech perception after cochlear implantation, but the open-set bisyllabic word recognition test is currently the only validated speech perception test in Finnish language, and thus used in this retrospective chart analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is in line with earlier results. 5 , 7 A possible limitation in the current study is the use of open-set bisyllabic word recognition test in quiet as a marker for speech perception and CI outcome in general. Other audiological tests, such as nonsense syllable, word, phrase or sentence tests, might de more appropriate in judging speech perception after cochlear implantation, but the open-set bisyllabic word recognition test is currently the only validated speech perception test in Finnish language, and thus used in this retrospective chart analysis.…”
Section: Discussionmentioning
confidence: 96%
“…6 While this method is noninvasive and can be used with children, its predictive value has thus far been insufficiently documented. In EECS measurements of CI candidates Neumann et al 7 found postoperative speech recognition to correlate with frequency differentation but not with other measured variables [sensations, threshold level, temporal difference limen (TDL), dynamic range]. Takanami et al 8 used EECS successfully in awake child patients with inner ear anomaly to demonstrate electroneural hearing before cochlear implantation.…”
Section: Introductionmentioning
confidence: 99%